Genomic organization of Borna disease virus. - Briese, T (1994)
Borna disease virus is a neurotropic negative-strand RNA virus that infects a wide range of vertebrate hosts, causing disturbances in movement and behavior. We have cloned and sequenced the 8910-nucleotide viral genome by using RNA from Borna disease virus particles. The viral genome has complementary 3' and 5' termini and contains antisense information for five open reading frames. Homology to Filoviridae, Paramyxoviridae, and Rhabdoviridae is found in both cistronic and extracistronic regions. Northern analysis indicates that the virus transcribes mono- and polycistronic RNAs and uses termination/polyadenylylation signals reminiscent of those observed in other negative-strand RNA viruses. Borna disease virus is likely to represent a previously unrecognized genus, bornaviruses, or family, Bornaviridae, within the order Mononegavirales.